Pengaruh Parameter Proses Milling pada Austempered Ductile Iron (ADI) Terhadap Kekasaran Permukaan Benda Kerja dan Chip Thickness Ratio - Rusnaldy, Rusnaldy; Umardani, Yusuf; Putra, Diva Tsamara; Bernard, Jovian (Mechanical Engineering Department - Semarang State Polytechnic, 2021)
Austempered ductile iron (ADI) is a difficult material for machining, even though ADI is believed to have several advantages such as strength, ductility, high toughness, fatigue resistance, good dynamic wear resistance, has a good strength-to-weight ratio, easy to manufacture and easy to cast that causes it to be widely used in various applications. This study investigates the effect of milling parameters on surface rougness and chip thickness ratio on milling of ADI. To produce ADI, ductile irons were first austenitized in furnace at 900oC for 1 hour and then they were quenched in salt bath at 375oC for 1 hour. The work material was machined with uncoated carbide tool. The tool was 20 mm in diameter. The cutting experiments were carried out in the dry mode. The feed was varied from 0.05 to 0.1 mm/tooth for cutting speed ranging from 15 m/min to 25 mm/min and depth of cut ranging from 0.1 mm to 0.3 mm. The surface roughness was measured using the Mitutoyo SJ-201, surface roughness machine. The chip thickness was measured using software Image J from the photograph produced by digital microscope endoscope. The results show that connected and loose chips were produced. Long and continuous chips were not found in this study. The effects of cutting speeds, feeds and depth of cut on surface roughness and chip thickness ratio are reported in this paper